REPRESENTASI NILAI - NILAI PENDIDIKAN ISLAM DALAM PERSEPEKTIF ABUDIN NATA DI PONDOK PESANTREN ZAINUL HASAN GENGGONG - Ferry Oktavian; Ahmad Khumaidi; Umi Lailia Maghfiroh (STKIP Pesisir Selatan, 2026)
This study aims toanalyze the representation of educational values from the perspective of Abuddin Nata at Zainul Hasan Genggong Islamic Boarding School, Probolinggo, particularly concerning the forms of educational values, the process of internalization, and their implementation in students’ daily lives. Thebackground of this study is based on the importance of Islamic education that focuses not only on the mastery of knowledge but also on the development of character, spirituality, morality, and social responsibility. This study employs aqualitative approach with acase study design. Theresearch subjects consist of the pesantren leaders, teachers (ustadz), administrators, and students (santri).Data were collected through observation, in-depth interviews, and documentation.Data analysis employed the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. Thefindings indicate that educational values are represented through four major aspects:faith (tauhid), morality (akhlak), knowledge, and discipline and responsibility. The value of faith is manifested through regular worship, Qur’anic recitation, dhikr, and other religious activities. Moral values are represented through exemplary conduct, respect for teachers, politeness, honesty, and social concern. The value of knowledge is manifested through kitab studies, formal education, deliberation, and discussion. Meanwhile, discipline and responsibility are developed through regulations, daily schedules, student organizations, and the assignment of responsibilities. Theimplication of this study is that pesantren culture serves as an effective medium for internalizing Islamic educational values.